2022
DOI: 10.1002/adem.202201050
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Phase Formation in Reactively Sputter‐Deposited La—Co—O Thin‐Film Libraries

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adem.202201050.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…[31,32] For reactively sputtered La-based oxide systems, there are only a few reports in the literature on similar columnar growth. A comparable structure formation was observed during hot sputter deposition of La-Co-O, [33] whereas nanostructure formation was observed for a Sr-and Ag-substituted La-Co-O system. [34,35] The SEM image in Figure 2b shows the columns in a pristine, as-grown state in top view.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…[31,32] For reactively sputtered La-based oxide systems, there are only a few reports in the literature on similar columnar growth. A comparable structure formation was observed during hot sputter deposition of La-Co-O, [33] whereas nanostructure formation was observed for a Sr-and Ag-substituted La-Co-O system. [34,35] The SEM image in Figure 2b shows the columns in a pristine, as-grown state in top view.…”
Section: Resultssupporting
confidence: 65%
“…[ 19–21 ] In a previous study, it was demonstrated that reactive combinatorial sputtering is an excellent method to fabricate and study La‐based perovskites. [ 22 ] It was shown that Mn is beneficial for the conductivity in La–Co‐perovskite films and hence crucial for electrocatalytic measurements. This was also reported by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, a single‐phase formation behavior was recently observed and described by the authors for reactive hot deposition of (La‐based) perovskites. [ 16 ] This phase formation behavior can be leveraged to synthesize phase‐pure perovskite MLs for a wide range of chemical compositions of the B‐sites. It can be described as a self‐organized growth process based on the perovskite stoichiometry, which suppresses formation of multiphase regions in favor of single‐phase perovskite.…”
Section: Introductionmentioning
confidence: 99%